1983
DOI: 10.1366/0003702834634055
|View full text |Cite
|
Sign up to set email alerts
|

Long Path Length Samples in Thermal Lens Calorimetry

Abstract: Laser-induced thermal lens calorimetry as applied to small absorbance determinations has traditionally relied upon the approximation that the sample behaves optically as a thin lens. The choice of a cell length which is not ideal for theory may be necessary for increased sensitivity. Two models for treating long samples of variable absorbance and enhancement are presented. The simpler of these is based on an approximation that such samples will behave according to the integrated position dependence of a thin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…If the focus of the pump laser is positioned in the center of the cell, then little signal enhancement would occur at cell lengths greater than 4 Rayleigh ranges. This behavior is quite different than that obtained for CW laser excited TLS(18).…”
contrasting
confidence: 92%
See 1 more Smart Citation
“…If the focus of the pump laser is positioned in the center of the cell, then little signal enhancement would occur at cell lengths greater than 4 Rayleigh ranges. This behavior is quite different than that obtained for CW laser excited TLS(18).…”
contrasting
confidence: 92%
“…The smaller beam waist will result in a reduced interaction length through the sample cell volume. Carter and Harris have calculated the effects of cell length on the CW laser TLS signal (18). In one of the methods utilized in the latter study, the interaction length was found to depend on the Rayleigh range or confocal distance of the focused laser.…”
Section: = R C S ' ( T ) X ( T )mentioning
confidence: 99%
“…This is because in this technique, the signal depends on the power density in the excitation laser beam. As a consequence, the signal intensity would not be doubled with the use of a cell with twice the path length (34,35) because in a long path length cell, the spot size of the laser beam will be enlarged as it propagates through the cell (34,35). The consequence of this spot size enlargement is the decrease in the laser power density and in the thermal lens signal because these two terms are known to be inversely proportional to the beam spot size.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the time constant tc also becomes longer. A longer measurement time is necessary, which as a consequence worsens the detection limit because the fluctuation in the laser intensity increases with time (34). Conversely, the beam spot size within each cell and the time constant remain the same with the use of the two-cell method developed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Not only would the linear flow velocity be lower, but the path length would be larger, both of which would increase the thermal lens sensitivity. Thermal lens calorimetry produces a signal which, to first order, is linearly related to path length (35). Very small path length cuvettes, roughly 100 jam wide or smaller, will produce low sensitivity.…”
Section: Resultsmentioning
confidence: 99%